Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
California Supreme Court Associate Justice Stanley Mosk giving his keynote address; Fresno County Young Lawyers Association President John McGregor looking on Star Palace lectern on table